Kumawus Tradition: Cultural Studies in the To' mbulu Sub-Ethnic Community, Walian Village, South Tomohon District in Tomohon City) - Burdam, Yohanes; Sholahuddin, Agus; Kridawati Sadhana, (Technium Social Sciences Journal, 2020)
Kumawus is a thanksgiving event after the death of a family member, which is also called a weekly event or maso itam (local dialect). Kumawus in its short meaning, namely making finished or bekeng finished (in the local language/dialect), which is doing something to the end related to the life of a family member who has died. The main objectives of this study are: (1). To explain the implementation of the Kumawus tradition historically according to the cultural views of the To' mbulu sub-ethnic in Walian Village, South Tomohon District, Tomohon City. (2). Describe the factors behind the tradition of implementing Kumawus in the To' mbulu sub-ethnic community in Walian Village, South Tomohon District, Tomohon City. This study uses a qualitative approach with grounded theory methods. This study used a qualitative approach with "Grounded Theory" analysis, which was developed by Strauss and Corbin, namely through the Coding procedure or Emik's perspective. The subjects of this research are the community, village leaders, traditional elders, church leaders in the Walian village, Tomohon City. Data collection techniques using observation, interviews, documentation, and literature study. The research instrument is the researcher himself as the main instrument. Based on the results of the research and discussion above, it can be concluded that: the procession of the Kumawus tradition in the grieving family of the To' mbulu sub-ethnic community in Walian Village, South Tomohon Subdistrict, Tomohon City, shows that there is interaction and togetherness and cooperation between communities which shows a strong appreciation of local cultural values community linkages and interactions in the implementation of Kumawus continue to run well even though Walian Village has been divided into two new sub-districts and a central village.